A transcriptome-guided genetic engineering strategy to balance cell growth with astaxanthin production in Phaffia rhodozyma - Jia, Jianping; Ye, Chenxi; Jin, Sainan; Li, Qingqing; Pan, Zhengyi; Wen, Wen; Bao, Guoliang (Frontiers in Microbiology, 2025)
Astaxanthin is a strong antioxidant and is widely applied in food industry. The yeast Phaffia rhodozyma is an ideal microbial astaxanthin resource. However, the nitrogen-deficiency stress, which is beneficial for astaxanthin synthesis, often impairs cell growth, leading to low productivity. In this study, an imbalance between cellular growth and astaxanthin synthesis in P. rhodozyma under nitrogen-deficient (H) and nitrogen-sufficient (L) conditions was identified. A comparative RNA-seq transcriptome analysis between the H and L groups revealed well-discriminated patterns. The differentially expressed genes (DEGs) indicated that the regulation of nitrogen deficiency does not occur directly in the astaxanthin biosynthesis pathway but rather operates at the global cellular level, involving processes such as central and energy metabolism, antioxidative stress responses, signal transduction, competitive metabolic pathways, and material transportation. Based on these findings, a regulatory mechanism is proposed, which involves cellular sensing of nitrogen sources in the medium, alterations in signaling pathways that direct effectors, and the regulation of multiple downstream target genes through post-translational modifications, protein interactions, gene transcription, and the protein and metabolite levels. Six DEGs were overexpressed in the wild strain (WT) of Phaffia rhodozyma, and the mutants M2 and M6, expressing the NHEJ gene for DNA repair and the ferric reductase gene, showed higher biomass and astaxanthin content compared with the WT strain under nitrogen-deficient conditions. However, the remaining mutants exhibited unchanged or even reduced biomass and astaxanthin productivity. Subsequently, a co-expression mutant (M7) carrying the two DEGs was constructed. This mutant exhibited further increases in both biomass and astaxanthin content, with 61.5 and 133.3% higher yields than the WT strain, respectively, and a 265.8% increase in final astaxanthin production.